2004
DOI: 10.2139/ssrn.556032
|View full text |Cite
|
Sign up to set email alerts
|

How Do Family Ownership, Control, and Management Affect Firm Value?

Abstract: Using proxy data on all Fortune-500 firms during 1994-2000, we find that family ownership creates value only when the founder serves as CEO of the family firm or as Chairman with a hired CEO. Dual share classes, pyramids, and voting agreements reduce the founder's premium. When descendants serve as CEOs, firm value is destroyed. Our findings suggest that the classic owner-manager conflict in nonfamily firms is more costly than the conflict between family and nonfamily shareholders in founder-CEO firms. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

89
1,342
11
34

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 812 publications
(1,476 citation statements)
references
References 45 publications
89
1,342
11
34
Order By: Relevance
“…Consequently, these initial results were extended to different markets and analysed in more refined ways. Villalonga and Amit (2006) in a study on Fortune 500 companies extend Anderson and Reeb's analysis and find different results.…”
Section: Family Firms and Performancementioning
confidence: 79%
See 2 more Smart Citations
“…Consequently, these initial results were extended to different markets and analysed in more refined ways. Villalonga and Amit (2006) in a study on Fortune 500 companies extend Anderson and Reeb's analysis and find different results.…”
Section: Family Firms and Performancementioning
confidence: 79%
“…Following extant literature on family firms and blockholders, a company is defined as being widely held if no shareholder holds more than 20% of ultimate voting rights (see among others Villalonga and Amit (2006), Sraer and Thesmar (2007)). Although a threshold of 20% may seem low, there exists a widely accepted view that due to generally low annual meeting attendance and active representation of blockholders either as chairman of the board or CEO in many companies, it is sufficient for having an influence on company policies and management.…”
Section: Ownership Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bloom and Van Reenen (2006) found that mismanagement will occur in particular if a business is transferred to the eldest son (primogeniture), whereas the management abilities will not be affected if the entire family appoints the management of a transferred business. In contrast, Morck, Shleifer, and Vishny (1989), Bennedsen, Nielsen, Pérez-González and Wolfenzon (2007), Pérez-González (2006) and Villalonga and Amit (2006) discovered in general a significantly poorer performance of companies run by heirs compared to firms with non-family executives. Grossmann and Strulik (2010) disapproved an inheritance tax privilege for businesses in a general equilibrium model.…”
Section: Pros and Cons For An Inheritance Tax Privilege For Businessesmentioning
confidence: 74%
“…See Villalonga and Amit (2006), Morck et al, (2000); Bennedsen et al (2007), Adams et al (2008), Perez-Gonales (2006). complementary to that of Michelacci and Schivardi (2008) and of Barba Navaretti et al (2008), who offer some evidence of the negative reactions of family firms to idiosyncratic risk.…”
mentioning
confidence: 99%